Michael J. Halvorson – Karen E. Spierling (eds.): Defining Community in Early Modern Europe.: Ashgate, Aldershot 2008, 372 s. - Čapská, Veronika (Lidé města, 2010)
A review of the book by Michael J. Halvorson and Karen E. Spierling.